Characteristics of atypical large well-differentiated hepatocellular carcinoma: a specific subtype of hepatocellular carcinoma?. Issue 4 (April 2020) - Okuno, Masayuki; Newhook, Timothy E.; Joechle, Katharina; Kawaguchi, Yoshikuni; De Bellis, Mario; Tzeng, Ching-Wei D.; Chun, Yun S.; Aloia, Thomas A.; Shindoh, Junichi; Kaseb, Ahmed O.; Vauthey, Jean-Nicolas
Abstract: Background: Hepatocellular carcinoma (HCC) de-differentiation is thought to correlate with size, therefore well-differentiated HCC ≥3 cm are considered rare and not fully understood. Methods: Patients who underwent hepatectomy for HCC between 1998–2016 were retrospectively analyzed. Patient's characteristics and recurrence-free (RFS) and overall (OS) survival were compared between those with atypical- (well-differentiated-HCC ≥3 cm) and typical-HCC (moderate-to-poorly-differentiated HCC ≥3 cm). Results: Of 176 patients included in this study, 37 (21%) had atypical-HCC. Patients with atypical-HCC were less likely to be Asian ethnicity (3% vs. 17%, p = 0.062), have lower rate of viral infection (14% vs. 43%, p = 0.003), cirrhosis (8% vs. 27%, p = 0.015). The tumors were less likely to demonstrate vascular invasion (30% vs. 59%, p = 0.002), and were associated with a lower alpha-fetoprotein level (3.5 ng/ml vs. 33.2 ng/ml, p < 0.001). Patients with atypical-HCC had a longer RFS (5-y RFS: 58.3% vs. 35.7%, p = 0.016) and OS (5-y OS: 79.1% vs 53.3%, p = 0.029) as compared to those with typical-HCC following univariate analysis, however this did not appear following multivariate analysis. Conclusion: Patients with atypical-HCC have different characteristic in terms of epidemiology, etiology, cirrhosis and vascular invasion as compared to typical-HCC. The etiology of atypical-HCC may be non-alcoholic fatty liver disease-related and/or malignant transformation of hepatocellular adenoma.